2010
DOI: 10.1152/ajpendo.00522.2009
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol modulates the macrophage migration inhibitory factor secretory pathway by regulating ABCA1 expression in human first-trimester placenta

Abstract: Successful pregnancy involves a series of events, most of them mediated by hormones and cytokines. Estrogens, besides being important for placental growth and embryo development, have a marked effect on the immune system exerting either pro- or anti-inflammatory properties. Numerous studies suggest that estrogens directly affect cellular function, including cytokine production. Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine involved in pregnancy, particularly during the earlier stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 59 publications
(78 reference statements)
1
20
0
1
Order By: Relevance
“…The BMI-R230C interactions observed only in pre-menopausal women suggest that these effects may be estrogen-related. Several lines of evidence are consistent with this finding: ABCA1 -diet interactions affecting HDL-C levels have been reported in pre-menopausal women [17], improved lipid profiles have been observed in response to estrogen [42][43], and estrogen increased ABCA1 expression in different tissues in both mice and humans [44][46]. The increased risk of these metabolic parameters in pre-menopausal women is again in discrepancy with their risk of CAD, and whether this has to do with other systemic effects of estrogen, and/or with pleiotropic effects of the R230C variant in platelets, endothelium, inflammatory or other cell types remains to be elucidated.…”
Section: Discussionsupporting
confidence: 78%
“…The BMI-R230C interactions observed only in pre-menopausal women suggest that these effects may be estrogen-related. Several lines of evidence are consistent with this finding: ABCA1 -diet interactions affecting HDL-C levels have been reported in pre-menopausal women [17], improved lipid profiles have been observed in response to estrogen [42][43], and estrogen increased ABCA1 expression in different tissues in both mice and humans [44][46]. The increased risk of these metabolic parameters in pre-menopausal women is again in discrepancy with their risk of CAD, and whether this has to do with other systemic effects of estrogen, and/or with pleiotropic effects of the R230C variant in platelets, endothelium, inflammatory or other cell types remains to be elucidated.…”
Section: Discussionsupporting
confidence: 78%
“…Although the cause of sex-related differences is not fully understood, estrogen is known to have an effect in premenopausal women by increasing HDL-C concentrations (37,38). Moreover, there is evidence that estrogen increases ABCA1 expression in different tissues (39,40) and estrogen therapy increases ABCA1 expression in leukocytes and improves lipid profile in menopausal women (41), suggesting that the sexspecific interaction here could be mediated by the effect of estrogen on ABCA1 expression. On the other hand, although testosterone is known to be responsible for lowering HDL-C levels in men (42), this hormone has been found not to affect apoA-I or ABCA1 expression in hepatocytes or human monocyte-derived macrophages (43), which is consistent with the lack of ABCA1-nutrient interaction observed in males.…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies on human placenta, Ietta et al (2010) demonstrated that low doses of E 2 stimulated MIF secretion, whereas higher doses downregulated it. Because BPA has weak estrogenic activity (Kuiper et al 1998, Rubin 2011, its stimulatory effect in MIF secretion observed here could be similar to that exerted by low doses of E 2 .…”
Section: Effect Of Bpa On Secretion Of Biomarkers Of Endometrial Matumentioning
confidence: 89%